Association of Peripheral Vascular Disease With Complications After Total Ankle Arthroplasty - Matthew S. Conti MD; Oleksandr Savenkov PhD; Scott J. Ellis MD (Foot & Ankle Orthopaedics, 2019)
Background: Despite limited evidence, peripheral vascular disease is often cited as a contraindication for total ankle arthroplasty. The purpose of our study was to identify whether peripheral vascular disease in patients undergoing total ankle arthroplasty increased the rate of infection, postoperative irrigation and debridement, or failure of the implant. Methods: The PearlDiver Database was used to identify Medicare patients who underwent a total ankle arthroplasty from 2005 to 2014. These data were then analyzed for postoperative infections within 90 days, subsequent irrigation and debridements, and failure of total ankle arthroplasties. A diagnosis of preoperative peripheral vascular disease only included those patients who had peripheral vascular disease as an ICD-9 diagnosis code and underwent a preoperative lower extremity angiogram prior to total ankle arthroplasty. Medical comorbidities were identified using ICD-9 diagnosis codes. Three multivariable logistic regression models were then developed in order to identify risk factors associated with postoperative infections and failure after total ankle arthroplasty. Results: A total of 10 698 Medicare patients who underwent a primary total ankle arthroplasty were identified. There were 334 patients who had a postoperative infection within 90 days of their total ankle arthroplasty, and 95 of those patients required an irrigation and debridement. Regression analysis demonstrated that patients with peripheral vascular disease had the greatest risk of developing a postoperative infection within 90 days (OR 2.85, P < .01), requiring an irrigation and debridement postoperatively (OR 4.87, P < .001), and having a total ankle arthroplasty failure at any time point postoperatively (OR 2.51, P < .001). Conclusions: Our study suggests that preoperative peripheral vascular disease is a significant risk factor for an acute postoperative infection, postoperative irrigation and debridement, and failure of the implant in Medicare patients undergoing a total ankle arthroplasty. Level of Evidence: Level III, therapeutic.